Kehadiran dalam Ibadah: Kajian terhadap Doa Pribadi dan Baca Alkitab Generasi Milenial dan Gen Z Berdasarkan Ibrani 10:25 - Sompotan, Dale Dompas; Hutagalung, Stimson Bernard (Institut Agama Kristen Negeri Palangka Raya, 2024)
This study conducts a comprehensive exploration of strategies aimed at elevating participation in worship, with a specific focus on the practices of personal prayer and reflection, especially within the Millennial and Gen Z demographics. The research methodology employs a rigorous exploratory analysis of biblical texts, particularly delving into Hebrews 10:25, and its practical application in the contexts of everyday life. Utilizing qualitative methods and a thorough literature review, this research meticulously gathers data through an in-depth analysis of various literary sources, including the Bible. The unequivocal findings of this research assert that personal prayer practices not only serve as catalysts but also constitute the core of heightened attendance in worship. Personal prayer imparts a deeper and more intimate spiritual dimension, harmonizing with the fundamental values encapsulated in Hebrews 10:25, emphasizing the significance of fellowship and active engagement in communal worship. Moreover, the study delineates the dynamic interplay of cultural and social shifts that shape the perspectives of the Millennial and Gen Z generations regarding spirituality and worship. The theological implications derived from these findings provide profound insights into the needs and challenges encountered by the younger generation in fortifying their spiritual connections in the modern era.